Probing the “Dark Matter” of the Human Gut Phageome: Culture Assisted Metagenomics Enables Rapid Discovery and Host-Linking for Novel Bacteriophages - Fitzgerald, C. Brian; Shkoporov, Andrey N.; Upadrasta, Aditya; Khokhlova, Ekaterina V.; Ross, R. Paul; Hill, Colin (Frontiers in Cellular and Infection Microbiology, 2021)
Recent years have been marked by the growing interest towards virulent and temperate bacteriophage populations inhabiting the human lower gastrointestinal tract – the gut phageome. A number of studies demonstrated high levels of specificity and temporal stability of individual gut phageomes, as well as their specific alterations in disease cohorts, in parallel with changes in the bacteriome. It has been speculated that phages might have an active role in shaping the taxonomic composition and functional properties of the human gut bacteriome. An overwhelming majority of gut bacteriophages, however, remain uncultured, unclassified, and their specific hosts and infection strategies are still unknown. They are often referred to as “the viral dark matter”. A possible breakthrough in understanding of the phageome can only become possible when a significant proportion of the “the viral dark matter” is identified and linked to bacterial hosts. Here, we describe a method that enables rapid discovery and host-linking of novel bacteriophages in the gut via a combination of serial enrichment cultures and shotgun metagenomics of viral DNA. Using this approach dozens of novel and previously known bacteriophages were detected, including the ones infecting difficult-to-culture anaerobic bacteria. The majority of phages failed to produce lysis and propagate on host cultures in traditional assays. The newly identified phages include representatives of Siphoviridae, Myoviridae, Podoviridae, and crAss-like viruses, infecting diverse bacterial taxa of Bacteroidetes, Firmicutes, Actinobacteria, Verrucomicrobia and Proteobacteria phyla. The proposed new method has a potential for high-throughput screening applications for mass discovery of new phages in different environments.